Integrating Qualitative Methods into Investment Climate Impact Evaluations - Mendoza Alcantara, Alejandra; Woolcock, Michael (World Bank Group, Washington, DC, 2015)
Incorporating qualitative methods into the evaluation of development programs has become increasingly popular in recent years, both for the distinctive insights such approaches can bring in their own right and because of their capacity to complement the strengths -- and where necessary correct some of the weaknesses -- of quantitative approaches. Some initial work deploying mixed methods has been undertaken in the assessment of investment climate reforms, but considerable room for expansion exists. This paper summarizes some of the key principles and practices underpinning mixed methods evaluations in development, highlight some notable examples of how such work has been conducted (and the particular contributions it has made), and offers some guidelines for those seeking to increase the sophistication and utility of qualitative methods in the evaluation of investment climate reforms.